2020
DOI: 10.1002/esp.4885
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lithology on channel geometry and bed sediment organization in mountainous hillslope‐coupled streams

Abstract: Lithology, channel geometry and bed sediment in mountainous streamsThe influence of lithology on channel geometry and bed sediment organization in mountainous hillslope-coupled streams Running Head: Lithology, channel geometry and bed sediment in mountainous streams

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 95 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…Grain size data come from a mix of published and new surveys. For the Elder Creek (NCCR) and OCR sites, we used existing bed sediment grain size surveys (Fratkin et al, 2020; Scheingross et al, 2013). Grain size data from the SGM and NSJM (Neely & DiBiase, 2020) are described in more detail in Section 4.2.4.…”
Section: Compilation Of Headwater Channel Morphologies In Steep Lands...mentioning
confidence: 99%
“…Grain size data come from a mix of published and new surveys. For the Elder Creek (NCCR) and OCR sites, we used existing bed sediment grain size surveys (Fratkin et al, 2020; Scheingross et al, 2013). Grain size data from the SGM and NSJM (Neely & DiBiase, 2020) are described in more detail in Section 4.2.4.…”
Section: Compilation Of Headwater Channel Morphologies In Steep Lands...mentioning
confidence: 99%
“…Increased sediment flux from earthflows appears to be mostly fine sediment; grain size surveys indicate high amounts of fine sediment and moderate coarse sediment loads in the North Fork tributaries with no significant difference between tributaries draining Teanaway and lower Roslyn formations, despite a rock strength difference between the basalt and friable sandstone (NFTWA, 1996). In a similar sandstone formation, Fratkin et al (2020) found significant variation in surface and subsurface grain size when compared with adjacent tributaries draining basalt; most bedload in their study area was delivered by debris flows and landslides. However, earthflows tend to incorporate highly weathered material and regolith; in the Eel River, 90 % of earthflow colluvium is smaller than 76 mm (Mackey and Roering, 2011).…”
Section: Landscape Disturbancementioning
confidence: 82%
“…The Scamander catchment offers a unique opportunity to investigate the influences of lithology on river channel form, with two sub‐catchments of similar size and differing geology, of far larger scale relative to similar comparisons (Fratkin et al, 2020; Johnson & Finnegan, 2015). GIS analysis of geological distributions showed that granite makes up 45% of the area of the upper Scamander and dominates the northern upper half of this sub‐catchment, allowing weathering products of quartz sand to influence downstream channels.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of catchments with many similar attributes but a few that are variable can give insights on bedrock controls of landscape evolution (DiBiase et al, 2018). Two gravel‐bed streams with contrasting lithology (basalt and sandstone) in Oregon showed varied channel shapes, slopes and riffle grain sizes, indicating that lithologic control on channel adjustment is driven by differences in rock competence (Fratkin et al, 2020). Two bedrock‐controlled streams in California showed very different planforms, one in sandstone being straight, and in mudstone being sinuous (Johnson & Finnegan, 2015), largely attributed to rock disintegration characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation